(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: The satisfaction survey of health workers helps the hospital’s Board of Directors understand their thoughts and aspirations, thereby building and adjusting the appropriate quality policies and building their loyalty and enthusiasm for the hospital. Objectives: Describe the satisfaction of health workers with the quality of medical examination and treatment services at district hospitals. Methods: Cross-sectional survey, quantitative research. Results: This study collected information from 300 health workers in six districts of the hospital in Thanh Hoa province through questionnaires. The results showed that health workers’ quality and satisfaction rates were relatively high, with scores and rates respectively (3.63 - 4.18 points) and (73% - 83.6%).